2011
DOI: 10.1038/eye.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

The impact of off the visual axis retinoscopy on objective central refractive measurement in adult clinical practice: a prospective, randomized clinical study

Abstract: Purpose The objective of this study was to examine the effect of the off axis retinoscopy on objective central refractive measurement in adult clinical practice. Methods In all, 40 subjects underwent undilated retinoscopy in a randomly selected eye both on and off the visual axis by a single masked examiner. Off axis retinoscopy was defined as retinoscopy performed with the testing eye of the examiner aligned with the contralateral (non-test) eye of the subject resulting in an off axis deviation in the nasal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To reduce variability, it is necessary to consider as a precedent that during the development of the retinoscopy protocol, it is essential to control the body posture and working distance during the rst four hrs to improve precision. Studies also established that those two elements are considered the principal source of error in retinoscopy [11,18]. A clear example is the variability detected between experienced teachers in retinoscopy that has been ±0,87 D and between trainees ±3,15 D [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce variability, it is necessary to consider as a precedent that during the development of the retinoscopy protocol, it is essential to control the body posture and working distance during the rst four hrs to improve precision. Studies also established that those two elements are considered the principal source of error in retinoscopy [11,18]. A clear example is the variability detected between experienced teachers in retinoscopy that has been ±0,87 D and between trainees ±3,15 D [25].…”
Section: Discussionmentioning
confidence: 99%
“…Body posture is corrected constantly, especially during the rst 4 hrs. A variation of just 5,58 degrees of visual axis is associated with a signi cative lens power error (this has been reviewed in myopes and astigmatic patients) [11]. b.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Tay et al . [ 11 ] found that the errors in refraction during off-axis retinoscopy were not statistically significant ( P = 0.068; paired t-test) when compared with on-axis retinoscopy. The present study found significant differences between each degree in off-axis retinoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 30 31 ] The size of the area of the retina involved in neutralization is small and reported as approximately 1/640 th the area of the optic disc, hence when performing retinoscopy on high myopes, even a small misalignment with the visual axis may induce spherical error in retinoscopic findings. [ 31 32 ] The effect of off-axis refraction was controlled in this study by (1) maintaining the same eye level between the examiner and the patient, (2) the trial frame was adjusted according to the interpupillary distance to avoid decentration, and (3) accurate centration of the reflex by aligning the streak across the vertical meridian of the patient. Furthermore, the best way to avoid transverse aberrations from influencing refraction is to neutralize the reflex across the largest visual zone and ignoring the reflex motion at the edges of the pupil.…”
Section: Discussionmentioning
confidence: 99%